Makna Wail dalam Al-Qur’an (Studi Analisis Tafsir Ringkas Kementerian Agama Republik Indonesia) - Munaliati, Munaliati; Supriadi, Akhmad Supriadi; Ade, Ade Afriansyah; Nisa, Nor Faridatunnisa (Faculty Ushuluddin, Adab, and Dakwah Institut Agama Islam Negeri (IAIN) Palangka Raya, 2025)
The Qur’an conveys messages of both promise and warning as recompense for human deeds, whether good or evil. One form of divine threat against reprehensible behavior is expressed through the term wail, which appears 27 times in various verses. This study examines the meaning of wail in the Concise Interpretation by the Ministry of Religious Affairs (Kemenag RI), addressing the research question: how is the term wail interpreted in this tafsir? The research employs a library-based, thematic, and descriptive-analytical method using a linguistic approach. The writing structure follows a thematic tafsir framework that explains the Qur’anic texts, messages, and guidance related to the term wail, and analyzes its interpretation within the context of the Kemenag tafsir. The findings show that the meaning of wail in the Concise Interpretation of Kemenag RI varies according to the verse and the human behavior it addresses. The term wail is interpreted as “destruction” for liars who fabricate falsehoods in the name of Allah; “woe” for sinners who deny Allah’s promises and power; “woe” for slanderers and backbiters; and “woe” for dishonest traders who cheat in measurement. Moreover, wail also means “destruction” for those who neglect their prayers and perform them lazily. Overall, the term wail in this tafsir reflects Allah’s stern warning against various immoral behaviors that disregard truth and piety.